2012
DOI: 10.3892/or.2012.1984
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of indoleamine-2,3-dioxygenase in cervical cancer cells suppresses tumor growth by promoting natural killer cell accumulation

Abstract: This study examined the role of the immunosuppressive enzyme indoleamine-2,3-dioxygenase (IDO) in cervical cancer progression and the possible use of this enzyme for cervical cancer therapy. We analyzed IDO protein expression in 9 cervical cancer cell lines (SKG-I, -II, -IIIa, -IIIb, SiHa, CaSki, BOKU, HCS-2 and ME-180) stimulated with interferon-γ. IDO expression was observed in all cell lines except for SKG-IIIb. We transfected the human cervical cancer cell line CaSki that constitutively expresses IDO with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…IDO is the unique rate‐limiting enzyme of the kynurenine pathway and leads to trypotophan depletion, which is sensitive to T cells, making T cells have to stay in G 1 phase of cell cycle and fail to proliferate . Otherwise, the metabolites produced in alternative degradation of tryptophan are toxic for NK cells by preventing their accumulation and growth . Besides the direct inhibiting effect, IDO can up‐regulate the Foxp3 expression on traditional CD4 + T cells to induce their transformation to Tregs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IDO is the unique rate‐limiting enzyme of the kynurenine pathway and leads to trypotophan depletion, which is sensitive to T cells, making T cells have to stay in G 1 phase of cell cycle and fail to proliferate . Otherwise, the metabolites produced in alternative degradation of tryptophan are toxic for NK cells by preventing their accumulation and growth . Besides the direct inhibiting effect, IDO can up‐regulate the Foxp3 expression on traditional CD4 + T cells to induce their transformation to Tregs .…”
Section: Discussionmentioning
confidence: 99%
“…14 Otherwise, the metabolites produced in alternative degradation of tryptophan are toxic for NK cells by preventing their accumulation and growth. 15 Besides the direct inhibiting effect, IDO can up-regulate the Foxp3 expression on traditional CD4 1 T cells to induce their transformation to Tregs. 36 IDO is the main mechanism of sustaining the stability of Tregs, for it can block the conversion of Tregs to TH17-like cells, especially in TDLNs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 Few studies have investigated the expression of IDO in cervical cancer. [26][27][28][29][30] Two such studies found higher levels of IDO expression in cervical cancer lesions as compared to normal cervical cells. 28,29 Fotopoulou et al, described less IDO activity in primary cervical cancer in comparison to samples from healthy individuals, but this study included only 20 patients.…”
Section: Introductionmentioning
confidence: 99%